2011
DOI: 10.4028/www.scientific.net/amm.121-126.226
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Adsorption Behavior of Amino Acid Corrosion Inhibitor on Cu (001) Surface

Abstract: Molecular dynamics simulation has been employed to investigate the adsorption behavior of glutamic acid and aspartic acid on Cu (001) surface, and the inhibition mechanism was also discussed. The results indicated that the two corrosion inhibitors could both adsorb on the Cu surface firmly due to the interaction between polar groups and surface. The two inhibitors both have excellent corrosion inhibition performance. However, the inhibition performance of glutamic acid is better than aspartic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…At the same time, amino acids, as metal corrosion inhibitors, are commonly used as corrosion inhibitors for various metals such as iron, copper, and aluminum [3] . Dai [31] and others used MD simulation to study the adsorption behavior of aspartic acid and glutamic acid on copper surfaces, and the results showed that glutamic acid had better performance. Kumar [32] and others used DFT calculations to study the corrosion inhibition behavior of four corrosion inhibitor molecules, including glutamic acid, to clarify their mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, amino acids, as metal corrosion inhibitors, are commonly used as corrosion inhibitors for various metals such as iron, copper, and aluminum [3] . Dai [31] and others used MD simulation to study the adsorption behavior of aspartic acid and glutamic acid on copper surfaces, and the results showed that glutamic acid had better performance. Kumar [32] and others used DFT calculations to study the corrosion inhibition behavior of four corrosion inhibitor molecules, including glutamic acid, to clarify their mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of inhibition was determined by the type and concentration of amino acid used. Work by Dai et al reported that glutamic acid and aspartic acid could inhibit corrosion on copper by adsorption onto the surface through their polar sites (39). Furthermore, glutamic acid has been shown to coordinate with metals by means of its two carboxyl groups and in turn, inhibit corrosion on steel.…”
Section: Corrosion Inhibitorsmentioning
confidence: 99%